Some aspects of periodontitis pathogenesis in children. - Shcherbina, I. N.; Kovach, I. V.; Dychko, Ye. N.; Taran, O. M. (Medicni Perspektivi, 2013)
Inflammatory processes in the tissues surrounding tooth root are frequent enough and develop as the direct complication of caries. As acute periodontitis is manifested with grinding toothache and violation of physiological act of chewing, symptoms of general intoxication, the continuous sluggish chronic periodontitis is harmful and dangerous to the organism as well. It forms the state of chronic оdontogenetic intoxication and chroneosepsis with wrong functioning of some internal organs and body systems. The like complications can cause significant disturbance to the function of kidneys, liver, heart, joints and their treatment without ablating focus of inflammation is often in- effective; this must be taken into account by doctors-interns. However, scanning of the oral cavity by conservative means has its difficulties mostly because of ignoring pathogenesis of such inflammation. That is why activity of ferments of blood dehydrogenases from the periapical tissues of the teeth affected with the chronic periodontitis was studied. The level of succinate dehydrogenase and alpha-glycerophosphate degydrogenase of lymphocytes of 110 schoolchildren aged 13-17 years old was studied. The main group of examined individuals included those of infected with tuberculousis – 50 individuals, and the control group (60 individuals) – clinically healthy ones without tuberculousis desease. All schoolchildren had 1 or 2 teeth affected with chronic periodontitis of the apical localization. The researchers found that a significant inhibition of activity of succinate dehydrogenase and alpha-glycerophosphate degydrogenase ferments occurs in the inflammatory periodontal tissues, which indicates to local immunity decline, and as a consequence, pathogenic bacteria activation. In people infected with tuberculousis these violations were  more developed. Such features of periodontitis pathogenesis must be taken into account when providing a combined treatment.